2015
DOI: 10.17795/intjsh-26742
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Testing a Model of Some Precedents and Outcomes of Borderline Personality Disorder in High School Students of Shiraz

Abstract: Background: Borderline Personality Disorder (BPD) characterized by emotion dysregulation, disturbed interpersonal relationship, unstable sense of self, affect and behavior, is a severe disorder with a reported suicide rate 50 times the general population. Objectives: The aim of this study was designing and testing a model for some antecedents and outcomes of borderline personality disorder. Patients and Methods:In this research child's attitude toward father and mother, early trauma, alexithymia, schema, disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The BPFS-C has shown good internal consistency across 12 months study by Crick et al ( 18 ), done on a sample of 400 students aged 10-12, (α > 0.76) as well as criterion validity ( 20 ) and construct validity ( 18 ). Prior research in Iran examining the 22-item instruments with a large community sample (n = 400) of boys and girls in high school showed high consistency (α > 0.84) ( 21 ). In the current study, Cronbach’s α was 0.83.…”
Section: Methodsmentioning
confidence: 99%
“…The BPFS-C has shown good internal consistency across 12 months study by Crick et al ( 18 ), done on a sample of 400 students aged 10-12, (α > 0.76) as well as criterion validity ( 20 ) and construct validity ( 18 ). Prior research in Iran examining the 22-item instruments with a large community sample (n = 400) of boys and girls in high school showed high consistency (α > 0.84) ( 21 ). In the current study, Cronbach’s α was 0.83.…”
Section: Methodsmentioning
confidence: 99%
“…After obtaining the consent from the participants, the patients with schizophrenia or other psychotic disorders were divided into first-episode psychotic patients and chronic psychotic patients based on the fact that they experienced the first episode of psychosis or had been experiencing it for more than 2 years, respectively [30]. Next, all participants of the three groups were assessed using DES [31] and Childhood Trauma Questionnaire-Short Form (CTQ-SF) [32] with the help of researchers. In contrast, Positive and Negative Syndrome Scale (PANSS) [33] was only performed to evaluate patients with schizophrenia and other psychotic disorders by an expert psychiatrist.…”
Section: Methodsmentioning
confidence: 99%
“…The Persian version of DES was employed to assess dissociative symptoms. In this 28-item questionnaire, participants are asked to score their experiences for each element based on a 10-point scale from never (0%) to always (100%) [31]. Sajadi et al [31] reported the Cronbach's alpha coefficient of this scale to be 0.92 for Persian cases.…”
Section: Desmentioning
confidence: 99%
“…In this 28-item questionnaire, participants are asked to evaluate their experiences for each element based on a 10-point scale from never (0%) to always (100%). Sajadi et al [38] reported the Cronbach's alpha coe cient of this scale to be 0.92 for Persian cases. Using factor analysis, they also showed three factor structures, i.e., dissociative amnesia, depersonalization/derealization, and absorption, and scored each of them separately.…”
Section: Desmentioning
confidence: 99%